Oil Consumption Forecasting using ARIMA Models: An Empirical Study for Greece - Dritsaki, Chaido; Niklis, Dimitrios; Stamatiou, Pavlos (International Journal of Energy Economics and Policy, 2021)
Oil is considered one of the most widely used commodity worldwide and one of the most important goods for a country's productivity. Even if the effect of renewable energy sources tries to replace the consumption of fossil fuels, such as oil, nonetheless the level of worldwide oil consumption hasn't changed. Forecasting oil consumption plays an important role on the designing of energy strategies for policy makers. This paper aims at modeling and forecasting oil consumption in Greece using Box-Jenkins methodology during 960-2020. Forecasting oil consumption was accomplished both with static and dynamic procedure, in and out-of-sample using various forecasting criteria. The results of our paper present a downturn in oil consumption for the following years due to two basic factors. The first is referred to Covid-19 pandemia where economic activity of the country decreased as well as business revenues. The second is the efforts made by the country to replace, oil consumption with other energy forms such as natural gas and mostly renewable sources like sun and wind. With these actions taken, the country – member of EU is consistent with the regulations signed to Kyoto protocol where there are commitments for CO2 reduction emissions and improvement of energy use. Keywords: Oil Consumption, ARIMA model, Box-Jenkins methodology, forecasting, Greece. JEL Classifications: C52, C53, Q43, Q47 DOI: https://doi.org/10.32479/ijeep.11231